Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4317/jced.52643
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous metastatic cutaneous squamous cell carcinoma and chronic lymphocytic leukaemia/small lymphocytic lymphoma in a cervical lymph node: Case report of an unusual event

Abstract: The synchronous occurrence of two different neoplasias is an uncommon event, which may arise between tumors originating in the same organ or in cancer-to-cancer metastasis. We report a rare case of chronic lymphocytic leukaemia / small lymphocytic lymphoma associated with a cutaneous metastatic squamous cell carcinoma in a cervical lymph node. In the affected lymph node, it was observed an effacement of the normal architecture by neoplastic lymphocytes and it was noted the presence of neoplastic invasive epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…On thorough review, all these cases involved male patients who ranged from 44 to 83 years of age [1]. Another case report, written seven years prior, stated that there have only been 11 reported cases of cutaneous SCC metastatic to tissues involving CLL/SLL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On thorough review, all these cases involved male patients who ranged from 44 to 83 years of age [1]. Another case report, written seven years prior, stated that there have only been 11 reported cases of cutaneous SCC metastatic to tissues involving CLL/SLL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the mechanism underlying the development of synchronous malignancies may be the result of cancer-to-cancer metastasis which is influenced by nonmodifiable factors such as age and genetic susceptibility or modifiable factors such as exposure to carcinogenic agents via environment or lifestyle habits. Furthermore, cancer-tocancer metastasis can be investigated by using specific immunohistochemical profiles [1]. Although many theories have been postulated, the exact mechanism has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swelling of the cervical lymph nodes may indicate lymphadenitis 5) , malignant lymphoma 15) , or lymph node metastasis 4) . In cases where the nodes are larger than 10 mm on postoperative computed tomography (CT) images of a malignant tumor, metastasis can be assumed.…”
Section: Introductionmentioning
confidence: 99%